Parallel implementation of Newton’s method for solving large-scale linear programs - Garanzha, V. A.; Golikov, A. I.; Evtushenko, Yu. G.; Nguen, M. Kh (Computational mathematics and mathematical physics, 2009)
Parallel versions of a method based on reducing a linear program (LP) to an unconstrained maximization of a concave differentiable piecewise quadratic function are proposed. The maximization problem is solved using the generalized Newton method. The parallel method is implemented in C using the MPI library for interprocessor data exchange. Computations were performed on the parallel cluster MVC-6000IM. Large-scale LPs with several millions of variables and several hundreds of thousands of constraints were solved. Results of uniprocessor and multiprocessor computations are presented.